INFORMATION COMPETENCE OF FUTURE RADIOIENGINEERS IN THE PROCESS OF PROFESSIONAL TRAINING - Жарова, О. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2014)
The problem of information competence of a future radiotricians in a technical university is considered. The basic elements of informative jurisdiction are described as experience of working with information, but not with its means, as ability to perceive means of information critically, to discover information, to estimate, to do a choice and to process it independently. As a result key jurisdictions which are included in the informatione competence must be formed during an educational process